Ayurveda Approach in Management of Avascular Necrosis (AYUSHDHARA, 2024)
Avascular necrosis (AVN) is a commonly encountered type of bone tissue death, presenting clinicians with multifaceted challenges in treatment. Effective management necessitates a delicate balance between preserving bone structure, restoring functionality, and relieving pain. Surgical interventions like drilling, bone graft insertion, and prosthetic placement are commonly pursued, yet their high cost and limited success rates underscore the need for alternative approaches. Exhibiting symptoms akin to disorders of musculoskeletal origin, AVN often manifests in a chronic stage, demanding comprehensive care. In Ayurveda, its clinical presentation and underlying pathology can be correlated with Asthi Majjakshaya (depletion of bone marrow), and Asthimajjagata Vata (Vata vitiation affecting bone and bone marrow). Ayurvedic management of AVN often involves Panchkarma therapies, (Shodhana i.e., eliminating toxins, restoring Doshik equilibrium, and rejuvenating the body) and medicinal intervention (Shamana i.e., pacifying Doshas within the body). Promising results viz., symptomatic improvements, revealed significant enhancements in pain relief, tenderness reduction, stiffness mitigation, and gait improvement underscoring the potential of Ayurvedic principles in providing substantial relief and enhancing the quality of life for individuals grappling with AVN. By incorporating Panchkarma therapies into the treatment of AVN, Ayurveda provides a holistic approach that not only alleviates symptoms but also targets the root causes contributing to the progression of the condition.